Resident alien. Season four [videorecording (DVD)] - Tudyk, Alan; Tomko, Sara; Reynolds, Corey, 1974-; Hogan, Peter; Parkhouse, Steve (Universal, 2026)
Based on the Dark Horse comics, "Resident Alien" follows a crash-landed alien named Harry and his life on planet Earth. Harry and his baby Bridget are stuck in prison on the Grey Moonbase, while a shape-shifting Alien called a Mantid has taken over his body on Earth passing himself off as the real Harry Vanderspeigle. Harry manages to escape the Greys and arrives back on Earth for a showdown with the Mantid Alien, but soon finds he may not have what he needs to finish the job.